(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The main aim of this research is to minimize the energy consumption of the sensor nodes in Wireless Body Area Network (WBAN) for green communication in smart health care systems using Improved Continuous Passive Motion (ICPM) protocol and compared with Continuous Passive Motion (CPM) protocol in WBAN. Materials and Methods:In this research energy efficient centralized green communication in a health care system is achieved using cluster based WBAN routing. In this scheme the cluster head (CH) and Innovative Commander Node (ICN) is selected using various parameters such as distance, residual energy, transmission and reception count. In this work there are two groups in which each group has 20 sample sizes collected by varying number of rounds and it was calculated by calculator. Net with pre-test power of 80% (G-power). To evaluate the effectiveness of the Enhanced ICPM protocol in terms of Lifetime, energy consumption, throughput and delay. Results: Energy Consumption and throughput has statistically significant value (p<0.05) from the SPSS results. The output obtained by the ICPM protocol has better performance when compared to the CPM protocol in terms of2.47% lower energy consumption, and 4.47% higher throughput. Conclusion: From the independent statistical T-test and experiment's results the proposed ICPM protocol has efficient routing when compared to CPM protocol.